Sin and Salvation: Exploring the Role of Psychological Stress and Acceptance/ Affirmation in Altered States of Consciousness - Hunter, John (My University, 2021)
The process of sin and salvation is central to Christianity. This process plausibly elicits psychological stress (including guilt, inadequacy, and fear) before replacing it with acceptance/ affirmation, and at the time of salvation individuals are told to anticipate “the gift of the Holy Spirit”. Through a deductive thematic analysis of accounts of a secular “transformation” ritual (a prevalent personal development seminar), it is demonstrated: (1) that these secular rituals elicit significant psychological stress (including guilt, inadequacy, and fear) for several days, before replacing this stress with acceptance/affirmation; and (2) that most participants of these rituals experience a distinct altered state of consciousness. Because ventromedial dopamine elevation has been identified as contributing to religiosity and religious experience, and because the symptoms of this secular altered state of consciousness are consistent with dopaminergic excitation, a biological mechanism for this phenomenon is theorized, and a natural explanation for the Holy Spirit is hypothesized.